Implementasi Model Pembiasaan Uswah Hasanah Kyai untuk Menumbuhkan Akhlak Santri Pondok Pesantren Al Istiqomah Kebumen - Muhammad Abdul Latif; Ngarifin Shidiq; Nur Farida (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
Muhammad Abdul Latif. The Implementation Of The Uswah Hasanah Habituation Model By Kyai To Develop The Moral Character Of Santri At Pondok Pesantren Al Istiqomah Kebumen. Undergraduate Thesis, Wonosobo: Faculty of Tarbiyah and Teacher Training, Al-Qur’an Science University of Central Java in Wonosobo, 2025. Uswah hasanah, which means good exemplary conduct, is a fundamental concept in Islamic teachings that greatly influences the development of individual personality and morality. In the Qur’an, particularly in Surah Al-Ahzab verse 21, Allah SWT affirms that the Prophet Muhammad SAW is the ultimate role model for humankind in all aspects of life. This concept is not merely a normative doctrine but a practical principle that can be implemented in everyday life, whether in the context of family, education, society, or leadership. This study aims to analyze the application of uswah hasanah values in contemporary life and their relevance in shaping a society of noble character.